The Impact of Pavement Conditions on Accident Severities - Baskara, Sudesh Nair; Haryati, Yaacob; Sitti Asmah, Hassan; Mohd Rosli, Hainin; Mohd Shahrir, Amin Ahmad; Putra Jaya, Ramadhansyah; Al-Saffar, Zaid Hazim (Suranaree University of Technology, 2023)
This paper focuses on the aspect of road safety based on the impact of pavement conditions on accident severities. Four models of binomial and multinomial logistic regression were produced using the R software and utilizing two years of accident and pavement conditions data on Malaysian highways. The surface characteristics analyzed included the International Roughness Index (IRI), rut depth (RD) and mean texture depth (MTD). The accident severity assessed ranged from damage to death. Results indicated that IRI has the highest tendency to affect accident severity for all models. At the thresholds identified for all independent variables, the chances of death had increased significantly. As such, efforts must be driven to ensure the thresholds are not reached in the maintenance of pavements for better road safety.